Analiza wpływu wielkości gospodarstwa na jakość parametrów produkcji - Mongiało, Zbigniew (Analysis of the Influence of a Farm Size on Quality of Production Parameters, 2006)
The paper deals with the correlation and regression analysis used to identify relations between certain output parameters regarding the milk farms. A number of statistically significant models that describe the relations have been found for the characters concerned. It is also shown that a quantity of cows may affect some parameters of the process under study.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 130-136